TYPES OF CODES SWITCHING - Rio Giovani Eyato (LP2M IAIN Sultan Amai Gorontalo, 2018)
The purpose of this study is describing the types of code switching spoken by teacher and students in teaching process. The research problem is what the types of code switching in the classroom are. The researcher uses descriptive qualitative approach as method for analyzing the data. The researcher collects the data by recording and writing on Table observation what teacher and students said in teaching-learning process, then collected it and classified. From the data analysis, the type of code switching which mostly was used by the teacher and the student during learning process was metaphorical code switching and situational code switching.